KONSEP ILMU SOSIAL PROFETIK DAN RELEVANSINYA TERHADAP PENDIDIKAN AGAMA ISLAM TELAAH PEMIKIRAN KUNTOWIJOYO - Widya Pratama, Adellia; Mulyadi, Acep (Turats, 2024)
Abstract: The study aims to determine how Kuntowijoyo thinks about the concept of prophetic social science and its relevance to Islamic religious education. The type of research used is Library Research, where the data sources are generated from various literature from books, articles or scientific papers written by Kuntowijoyo, and others that are related to a problem to be discussed. The results of the study indicate that prophetic social science has three main values, namely: (1) Humanization related to the formation of attitudes, morals and personality of a person in order to reduce acts of violence (2) Liberation, liberation to be able to open the horizons of thought of students (3) Transcendence, will lead to the ideals of prophetic ethics desired by Kuntowijoyo. Returning human nature to God through Islamic religious education with a monotheistic approach in order to become a stronger and more responsible person, where the three values ​​are relevant to Islamic religious education.